Making sense of consumer inflation expectations: The role of uncertainty - Lovisa Reiche; Aidan Meyler (European Central Bank (ECB), 2022)
Consumers' inflation expectations play a key role in the monetary transmission mechanism. As such, it is crucial for monetary policymakers to understand what they are and how they are formed. In this paper we introduce the (un)certainty channel as means to shed light on some of the more puzzling aspects of reported quantitative inflation perceptions and expectations. These include the apparent overestimation of inflation by consumers as well as the negative correlation observed between the economic outlook and inflation expectations. We also show that the uncertainty framework fits with some of the stylised facts of consumers' inflation expectations, such as their correlation with socio-demographic characteristics and economic sentiment.
Keywords: D11; D12; D84; E31; E52; 330; Inflation; Expectations; Uncertainty; Consumers